HIV-related excess mortality and age-related comorbidities in patients with HIV aged ≥60: a relative survival analysis in the French Dat'AIDS cohort. Issue 1 (25th January 2019) - Hentzien, Maxime; Dramé, Moustapha; Delpierre, Cyrille; Allavena, Clotilde; Cabié, André; Cuzin, Lise; Rey, David; Pugliese, Pascal; Hédelin, Guy; Bani-Sadr, Firouzé
Abstract : Objective: The objective was to evaluate the association between age-related comorbidities (ARCs) and 5-year HIV-related excess mortality in people living with HIV aged ≥60 years. Design: Cohort study using relative survival analysis (Estève's model). Setting: The French multicentre prospective Dat'AIDS cohort that involves 12 French hospitals. Participants: Inclusion of 1415 HIV-1 infected patients actively followed aged ≥60 years on January 2008, with a 5-year follow-up period in the late combination antiretroviral therapy era. Results: Among 1415 patients included, 154 died. By multivariable analysis, factors predictive of 5-year HIV-related excess mortality were non-AIDS-related cancer (adjusted excess HR (aEHR)=2.94; 95% CI 1.32 to 6.57), cardiovascular disease (aEHR=6.00; 95% CI 2.45 to 14.65), chronic renal disease (aEHR=4.86; 95% CI 2.24 to 10.53), cirrhosis (aEHR=3.58; 95% CI 1.25 to 10.28), hepatitis C co-infection (aEHR=3.63; 95% CI 1.44 to 9.12), body mass index<18.5 kg/m² (aEHR=4.10; 95% CI 1.61 to 10.48) and having a CD4 cell count ≤200/mm 3 (aEHR=5.79; 95% CI 2.28 to 14.69). Conclusions: ARCs, particularly cardiovascular disease and chronic renal disease, are predictive of HIV-related excess mortality, with an increase in hazard similar to that of CD4 cell count. Trial registration number: NCT02898987 .